(untitled) (KULT_online, 2010)
The present book focuses on one of Hitler’s most important helpers. Renowned NS scholar Peter Longerich tries to unravel the difficult personality of Heinrich Himmler and the motives behind his deeds. The author exceeds the genre of ’political biography’ and looks at the whole life of Himmler in different stages of its political as well as private facets. He combines structural history and biography, and retraces chronologically and synoptically the different activities Himmler initiated as Reichsführer SS, chief of the Polizei, Commissar for the Strengthening of Germandom, Minister of the Interior, and commander of the reserve army. In doing this, the book shows that the individual political fields for which Himmler was responsible were much more strongly connected to each other than one had previously thought.